In situ encapsulation of metal sulfide into hierarchical nanostructured electrospun nanofibers as self-supported electrodes for flexible quasi-solid-state supercapacitors. Issue 2 (13th December 2021) - Yao, Mengyao; Guo, Chaofei; Zhang, Yifan; Zhao, Xin; Wang, Yong
Abstract : "Tube-on-fiber" carbon-encapsulated metal sulfide (Co–S@CNF–CNT) is designed and exhibits good flexibility and outstanding electrochemical performance for flexible supercapacitors. Abstract : Flexible freestanding electrodes, with high electrochemical performance and long cycle stability, are the key units essential to realizing flexible solid-state supercapacitors and fulfilling the demand for portable electronic equipment. Herein, we report hierarchical "tube-on-fiber" nanostructures synthesized via melamine-assisted calcination and vulcanization processes on electrospun fibers, composed of zeolitic imidazolate framework-67 and polyacrylonitrile. The hierarchical nanostructure is devised to prevent the agglomeration of Co-mixed cobalt sulfide nanoparticles, and the in situ growth of Co-catalyzed carbon nanotubes (CNTs) on carbon nanofibers is extremely beneficial to improving electronic conductivity. Based on these advantages, the hierarchical nanostructured composite of carbon-encapsulated metal sulfide (Co–S@CNF–CNT-3) delivers a large mass-specific capacitance of 416.5 F g −1 at 0.2 A g −1 . In addition, a quasi-solid-state asymmetric supercapacitor with Co–S@CNF–CNT-3 as the cathode and C@CNF–CNT-3 as the anode (defined as Co–S@CNF–CNT-3//C@CNF–CNT-3) is assembled. It shows a high energy density of 10.3 Wh kg −1 with a power density of 320 W kg −1 at 0.4 A g −1 or a superior power density of 8000 W kg −1 with an energy density of 7.56 Wh kg −1 at 10 A g −1 . Furthermore, the assembled hybrid supercapacitor shows an outstanding capacitance retention of 96.9% after 10 000 cycles at 5 A g −1 and good mechanical flexibility, illustrating its promising potential for practical flexible supercapacitors.